Prognostic Value of the Modified Systemic Inﬂammation Score in Patients With Extranodal Natural Killer/T-Cell Lymphoma - Huang, He; Chen, Li Min; Fang, Xiao Jie; Guo, Cheng Cheng; Lin, Xiao Ping; Hong, Huang Ming; Li, Xi; Wang, Zhao; Tian, Ying; Chen, Mei Ting; Yao, Yu Yi; Chen, Zegeng; et al. (Frontiers in Pharmacology, 2020)
Abstract Background: Extranodal natural killer/T-cell lymphoma (ENKTL) is a rare and extremely malignant tumor.The systemic inﬂammation score (SIS),which is based on the pretreatment level of lymphocyte-to-monocyte ratio (LMR) and serum albumin (Alb),has been shown to be of prognostic value in a number of cancers.We integrate several other pretreatment serum inflammatory indicators,including the neutrophil-to-lymphocyte ratio (NLR),lymphocyte-to-monocyte ratio (LMR),serum C-reactive protein (CRP) and albumin (Alb) level,to establish a modified systemic inflammatory scoring system to predict clinical outcomes of ENKTL. Methods: A total of 184 patients with newly diagnosed ENKTL was retrospectively investigated.Systemic inflammatory indexes,including NLR,LMR,CRP and Alb level were reviewed.Receiver operating characteristic (ROC) curve analysis was carried out to obtain the optimal cut-off value.The associations between cutoff values and overall survival (OS) were analyzed by Kaplan–Meier curves and Cox proportional models. Results:The median age of patients was 44.0 years,ranged from 15 to 82 years.There were 129 (70.1%) male patient.About 57.1% of patients had stage III or IV disease.The optimal cut-off values of NLR and LMR in predicting OS were 3. 1 and 2.4,respectively.The clinical standard of CRP and Alb levels at 10mg/L and 40mg/L respectively,were chosen as the optimal cut-off values.By multivariate analysis,hemophilic syndrome(HR:10.540,95% CI: 3.440-32.291,P<0.001),advanced Ann Arbor stages (III–IV) (HR: 4.606,95% CI: 1.661-12.774,P=0.003), paranasalsinus invasion(HR:2.323,95%CI:1.069-5.047,P=0.033),NLR≥3.1(HR: 3.019,95%CI: 1.317-6.923,P= 0.009), Alb level <40mg/L(HR:0.350,95%CI:0.134-0.915,P= 0.032) and radiation therapy(HR: 0.430,95% CI: 0.205-0.901,P=0.025) were independent protective factors for ENKTL.We combined two inflammatory indexes NLR and Alb level to establish a modified systemic inﬂammation score (mSIS).These 184 patients were divided into 3 groups: Group 1 (mSIS score 0),Group 2 (mSIS score 1),Group 3 (mSIS score 2).The mean OS of these three groups were 42 months((95% CI 31.4-53.12), 77 months((95% CI 68.5-87.5),and 89 months(95% CI 71.4-82.7) respectively (P < 0.001).The Harrell’s concordance index (C-index) of mSIS is 0.725.The mSIS could be used to discriminate patients categorized in the low-risk group of International Prognostic Indexs (IPI) (P<0.001) and the low-risk and intermediate-risk prognostic index of natural killer cell lymphoma (PINK) group (P = 0.019). Conclusion:The pretreatment mSIS could be an independent prognostic factor for OS in patients with ENKTL and warrants further research.